Nurse of family’s health program under the use view - Vasconcelos, Alexsandra Cabral; Moura, Escolástica Rejane Ferreira (Rev Rene, 2003)
The study had as objective identify perceptions of users of a attached area of the Family’s Health Program (FHP) on the nurse’s performance; to recognize the activities developed for this professional from the users’ words and to analyze its performance based on the lines of direction of the FHP.  It has been done an interview with 120 users (representative of 20% of the area’s families), in October of 2002. The nurse had is professional identity adequately recognized for 95,8% of the sample; the nursing consultation was identified as its main activity in the FHP, followed by the domiciliary visit. The nurse remains harnessed to the biomedical model, centered in the individual attendance and in consultations.